The vaccine hesitancy continuum among hesitant adopters of the COVID‐19 vaccine - Ramey Moore; Rachel S. Purvis; Don E. Willis; Kyle C. Worley; Devonte Hervey; Sharon Reece; Aimee Yeates; Pearl A. McElfish (Clinical and Translational Science, 2022)
Abstract Vaccination is a strategy for mitigating the impact of coronavirus disease 2019 (COVID‐19) at both the individual and population levels. Vaccine hesitancy is identified as a significant threat to global health by the World Health Organization (WHO). Vaccine hesitancy has been theorized as a continuum encompassing a range of attitudes, beliefs, emotional orientations, ideologies, and health‐seeking behaviors. Individuals who received the COVID‐19 vaccine but also indicated some level of hesitancy about vaccination, or “hesitant adopters,” remain an understudied group. This study uses a qualitative descriptive design to understand motivations to receive the COVID‐19 vaccine among hesitant adopters at various self‐reported levels of hesitancy. We conducted interviews with hesitant adopters (n = 49) to analyze the elements of vaccine hesitancy corresponding to reported levels of COVID‐19 vaccine hesitancy (i.e., “little hesitant,” “somewhat hesitant,” and “very hesitant”). Concerns about side effects are shared across the continuum but are articulated differently at each level of hesitancy. The “little hesitant” relate fears of side effects to their health and a lack of clear information to inform their health decision making, whereas the “very hesitant” articulate the risks of side effects within the frame of conspiracies related to the development, approval, and economics of the COVID‐19 vaccine. Additionally, conspiracy theories generally increase in salience across the continuum, with the “very hesitant” reporting conspiracy theories as the most salient element of vaccine hesitancy. This research presents opportunities for developing targeted interventions for different levels of vaccine hesitancy.